A Brief Study about Golden Proportion - Tripuravaram V. K. Reddy; Sihivahanan Dhanasekaran (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
The Golden Proportion has long been thought to be perfect, ideal, and desirable, and it has been used by engineers and architects to study beauty and design patterns and proportions. It has been proposed that the golden proportion is a useful tool for the evaluation of symmetry, dominance, and proportion in the diagnosis of tooth arrangement and in the application of esthetic dental treatment. A dental surgeon should be aware of the golden proportion as a design element. Understanding this enigmatic proportion that has long been associated with beauty may provide us with useful guidelines that can be combined with our existing knowledge and applied to our dental work to restore dental aesthetics with reasonable assurance of success. The golden proportion is a constant that mathematically defines the ratio between the dimensions of a larger and a smaller length.